2023
DOI: 10.1111/bju.16220
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy vs retrograde intrarenal surgery for renal stones: a Cochrane Review

Leah Soderberg,
Onuralp Ergun,
Maylynn Ding
et al.

Abstract: ObjectivesTo assess the effects of PCNL versus retrograde intrarenal surgery (RIRS) for the treatment of renal stones in adults.MethodsWe performed a comprehensive search of the Cochrane Library, MEDLINE, Embase, three other databases, trials registries, other sources of the grey literature, and conference proceeding up to March 23, 2023. We applied no restrictions on publication language or status. Screening, data extraction, risk of bias assessment and certainty of evidence (CoE) rating using GRADE were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This makes logical sense, in that a long, narrow and steep lower pole is unlikely to be amenable to ureteroscopy, and therefore a percutaneous approach ought to be considered. A recent Cochrane review has suggested that PCNL may improve the SFR compared to ureteroscopy, with little effect on major complications and reduced need for secondary interventions, albeit with low certainty of evidence [ 30 ]. However, the IPA was not considered and therefore there may yet be a role for ureteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…This makes logical sense, in that a long, narrow and steep lower pole is unlikely to be amenable to ureteroscopy, and therefore a percutaneous approach ought to be considered. A recent Cochrane review has suggested that PCNL may improve the SFR compared to ureteroscopy, with little effect on major complications and reduced need for secondary interventions, albeit with low certainty of evidence [ 30 ]. However, the IPA was not considered and therefore there may yet be a role for ureteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous nephrolithotomy (PCNL) has the superior e cacy and highest rate of monotherapeutic success in renal stone management. However, it is also associated with higher risk of injuries and complications when compared to extracorporeal shock wave lithotripsy (ESWL) and exible ureteroscopy [2,3]. According to the European Association of Urology (EAU) guidelines, PCNL is the primary treatment option for renal stones of size > 2 cm as well as lower pole stones > 1 cm [4].…”
Section: Introductionmentioning
confidence: 99%